Enhancing English Language Teaching: Workshop Program for EFL Teachers in Surakarta - Joko Nurkamto; Teguh Sarosa; Hefy Sulistyowati; Dewi Sri Wahyuni; Kristiandi; Lastika Ary Prihandoko (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The workshop program addresses the significance of effective English language teaching and identifies a knowledge gap in the implementation of the Merdeka Curriculum. Drawing on current literature, it emphasizes the need for transformative professional development for EFL teachers to excel in their pedagogical practices. The workshop program aims to equip EFL teachers with the knowledge and skills necessary to create dynamic and inclusive English language classrooms. By focusing on student-centered learning and project-based approaches, the program aims to enhance students' language proficiency and critical thinking abilities. The workshop employs interactive and hands-on learning methods, encouraging collaborative discussions, role-playing, and practical exercises. Experienced facilitators and experts in language education lead the sessions, ensuring an engaging and supportive learning environment. Through the workshop program, EFL teachers gain a comprehensive understanding of the Merdeka Curriculum and its student-centered nature. They learn to integrate CEFR standards effectively, differentiate instruction, and implement formative and summative assessments. Moreover, teachers gain insights into overcoming challenges related to curriculum transition and student diversity. By participating in the workshop program, EFL teachers can elevate the quality of English language teaching in their classrooms, fostering a generation of confident communicators and critical thinkers.